Flow injection amperometric nitrite sensor based on silver microcubics-poly (acrylic acid)/poly (vinyl alcohol) modified screen printed carbon electrode. (1st April 2017) - Promsuwan, Kiattisak; Thavarungkul, Panote; Kanatharana, Proespichaya; Limbut, Warakorn
Graphical abstract: Abstract: This work reports an electrochemical sensor for the nitrite determination by using flow injection amperometry (FI-amp) based on a screen printed carbon electrode (SPCE) modified with silver microcubics-polyacrylic acid/poly vinyl alcohol (AgMCs-PAA/PVA). The AgMCs-PAA was synthesized via a simple chemical reduction method. The prepared AgMCs-PAA/PVA modified SPCE displayed excellent electrocatalytic properties for the oxidation of nitrite and increased the catalytic current response. Under the optimum conditions, the sensitivity of the AgMCs-PAA/PVA/SPCE was 1.6, 4.9 and 1.2 times higher than the bare SPCE, PVA/SPCE, and Ag/PVA/SPCE, respectively. This sensor exhibited a rapid amperometric response to the oxidation of nitrite, which allowed it to be used for the determination of nitrite with a linear range from 2.0 μM to 800.0 μM with a limit of detection and a limit of quantification of 4.5 and 14.9 μM, respectively. This propose nitrite sensor had a high sensitivity (474.14 μAmM -1 cm -2 ), good repeatability (RSD < 6%, n = 6), stability (RSD = 3%, n = 120) and good accuracy (recovery = 84 ± 3 to 102 ± 1%). This method successfully detected nitrite in meat products and the results were consistent with those obtained with the standard spectrometer method. It is possible to apply the proposed method to detect nitrite in other foods and in the environment.